A novel scheme for lossless authenticated multiple secret images sharing using polynomials and extended visual cryptography - Krishnaraj Bhat; Uday Kumar Reddy K.R.; Ranjan Kumar H.S.; Dindayal Mahto (IET Information Security)
Abstract Researchers have put forward many variations of schemes for secret image sharing on grounds of visual cryptography and polynomials. The authors of this paper put forward a novel scheme for sharing multiple secret images with perfect reconstruction and authentication for cheating prevention. The perfect reconstruction of all shared secret images is obtained by applying polynomial‐based encryption and decryption, and one‐time authentication is done for all shared secret images by stacking the intelligible shares created by using extended visual cryptography. Properties' analysis, experimental results and comparisons are given to exhibit the potency of the scheme.